Pengaruh Penambahan Limbah Abu Pembakaran Serbuk Kayu Terhadap Kuat Tekan Paving Block - Jheinjil Buttu; Yoga Charol Vincenthius Tethool; Rio Oktovinary Pramanagara (Universitas Papua, 2023)
Paving blocks are building materials used as road surface pavements, both for the purposes of vehicle parking lots, sidewalks, and for decorative purposes of making parks and so on. Wood powder is a type of waste material that is organic in nature which is waste found in the sawmill industry environment which is currently not optimally utilized, the chemical compounds present in sawdust ash so that it can be used as an added ingredient in paving block mixtures are silica compounds (Si02) which are chemicals that can improve the quality of concrete, due to reactions that occur between silica and free lime in the concrete mix. In the process of making paving blocks using a mixture variation of 0%, 5% and 10% with the addition of sawdust ash to the number of test objects with 9 pieces and the pressure test and water absorption were carried out at the age of 28 days of curing. At the addition of 10% eucalyptus dust close to the minimum quality requirements with the provisions of 8.5 MPa (SNI 03-0691-1996). In this variation the bonding that occurs between the silica produced and calcium hydroxide has reached its optimum point. The effect of adding eucalyptus dust in the paving block mixture for water absorption at a percentage of 0% was 9.42%, 5% was 10.16%, and 10% was 10.64%. So the average water absorption above is classified as D quality which is used for parks and other uses.